Karakteristik Campuran AC-WC Menggunakan Batu Sungai Sarambu Bittuang Kabupaten Tana Toraja - Yosua Surya Parura (Paulus Civil Engineering Journal, 2025)
Asphalt mixtures has a crucial role in road pavement. Tana Toraja Regency has Sarambu Bittuang River Stone resources that have the potential to be used in AC-WC mixtures. This research aims to determine the composition for AC-WC mixtures through conventional Marshall testing and to obtain the results of the Retained Marshall Stability of the AC-WC mixture from Sarambu Bittuang River Stone. The testing included Marshall Immersion. The research method included testing the characteristics of the aggregate (Los Angeles abrasion test, gradation, and Marshall testing (stability, flow, VIM, VMA, and VFB) according to the 2018 Bina Marga General Specifications. The findings of the research are that the Optimum Asphalt Content (OAC) is 7.00%, with the mixture composition being coarse aggregate 32.59%, fine aggregate 57.23%, and filler 3.18%, and the Retained Marshall Stability value is 95.89%, indicating that this mixture demonstrates good resistance to immersion.